Highly stable Zn-MOF with Lewis basic nitrogen sites for selective sensing of Fe3+ and Cr2O72− ions in aqueous systems. Issue 17 (11th October 2020) - Yin, Jia-Cheng; Li, Na; Qian, Bin-Bin; Yu, Mei-Hui; Chang, Ze; Bu, Xian-He
Abstract: A luminescent Zn(II)-based MOF, [Zn(dptz)(BDC)(H2 O)]n [1, dptz = 3, 6-di(1H-pyrazol-4-yl)-1, 2, 4, 5-tetrazine, H2 BDC = terephthalic acid], with Lewis basic nitrogen sites has been synthesized by a solvothermal method. Using ligands with higher p K a value, complex 1 exhibits excellent solvent and pH stabilities in the pH range 2–12. 1 can serve as a highly sensitive and efficient luminescent probe for detecting Fe 3+ and Cr2 O7 2− ions in aqueous systems. The values of K SV toward Fe 3+ and Cr2 O7 2− were estimated to be 1.61 × 10 3 M −1 and 1.26 × 10 4 M −1, respectively. The possible sensing mechanism has been discussed. All these results suggest 1 is a promising dual-functional luminescent sensor for the detection of Fe 3+ and Cr2 O7 2− ions in aqueous solution. Graphical Abstract: